Brønsted Base-Mediated Aziridination of 2-Alkyl-Substituted-1,3-Dicarbonyl Compounds and 2-Acyl-Substituted-1,4-Dicarbonyl Compounds by Iminoiodanes - Tejo, Ciputra (2017)
The synthesis of α,α-diacylaziridines and α,α,β-triacylaziridines from reaction of 2-alkyl-substituted-1,3-dicarbonyl compounds and 2-acyl-substituted-1,4-dicarbonyl compounds with arylsulfonyliminoiodinanes (ArSO2N=IPh) under Brønsted base-mediated atmospheric conditions is described. The reaction mechanism is thought to involve the formal oxidation of the substrate followed by aziridination of the ensuing α,β-unsaturated intermediate by the hypervalent iodine(III) reagent.